Curbing the HIV/AIDS Epidemic in Djibouti - El-Saharty, Sameh; Ravano, Wendy V.; Ali, Omar; Abdel-Rahmane, Maissa (World Bank, Washington, DC, 2017)
This study outlines the initial challenge presented by the HIV/AIDS epidemic, describes Djibouti's response, reviews the results achieved and the enabling factors in curbing the spread of the epidemic, and identifies remaining challenges. Between 2002 and 2008, HIV prevalence among young pregnant women aged 15-24 was reduced from 2.7 percent to 1.9 percent and among sentinel surveillance groups from 2.5 percent to 1.9 percent. HIV prevalence among tuberculosis patients was reduced from an estimated 22 percent to 12 percent. Condom use during last intercourse outside marriage increased from 27 percent to 55 percent and reached 95 percent among sex workers. Among the general population, awareness of HIV/AIDS increased to 95 percent and knowledge about transmission and prevention rose to 50 percent. Political commitment, engagement of community and religious leaders, rigorous communication, social marketing and the provision of an integrated package of medical and social services, and donor harmonization were among the key factors that contributed to the achievement of these results. Despite these impressive results in a relatively short period, Djibouti still has to address several challenges and consolidate program gains, but most importantly, funds are being mobilized from government resources to sustain the national AIDS control program.